Whole fractions from probiotic bacteria induce in vitro Th17 responses in human peripheral blood mononuclear cells. (September 2018) - Hidalgo-Cantabrana, Claudio; Lucena-Prieto, María Rosa; Moro-García, Marco Antonio; Alonso-Arias, Rebeca; Sánchez, Borja
Graphical abstract: Highlights: Bacterial extracts from probiotics species modulate human immune response. The bacterial DNA was the most immunogenic fraction. The DNA induce a Th17-like response in human PBMCs. Bacterial fractions can be used to modulate the immune response to improve the gut barrier. Abstract: Probiotics are used to improve human health due to their capability to induce beneficial effects in gastrointestinal diseases and modulate the immune response. However, scarce information is known about the bacterial active compounds and the metabolic pathways of interaction with immune cells. In the present study, we analyzed the immune response elicited by surface-associated proteins, the whole surface extract (WSE) and the genomic DNA of three strains from the main representative probiotic species for human consumption, L. acidophilus DSM20079 T, L. rhamnosus GG, B. longum NCIMB 8809, using an in vitro model of human PBMCs from healthy donors. Eighteen cytokines were quantified using Luminex Technology to understand the immune pathways modulate by bacterial extracts. Overall, the bacterial fractions elicited a different immune response in PBMCs, whereas the isolated DNA was able to induce a higher Th17-like response that could lead to a protective effect in the epithelial barrier function.